2020
DOI: 10.1094/pdis-01-20-0040-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Pear Chlorotic Leaf Spot-Associated Virus, a Novel Emaravirus Associated with a Severe Disease of Pear Trees in China

Abstract: Pear chlorotic leaf spot (PCLS) is a recently emerged disease of commercially cultivated sandy pear (Pyrus pyrifolia) trees in central and southern China. By integrating high-throughput sequencing (HTS) and conventional Sanger sequencing of RT-PCR products, a novel emaravirus infecting pear trees is identified and molecularly characterized. The virus is provisionally named pear chlorotic leaf spot-associated virus (PCLSaV). PCLSaV shows the typical molecular features of members of the genus Emaravirus in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…The P1-P4 proteins encoded by GEVA were presumed to be the viral RdRp, GP, CP, and MP due to the presence of similar domains and motifs in homologous proteins from other emaraviruses, however, there was low overall sequence identity of P1-P4 from GEVA with these proteins from other emaraviruses. Furthermore, the phylogenetic tree of RdRp, GP, CP, and MP showed that GEVA was positioned in subgroup I of Emaravirus, as reported by Liu et al (2020), but which was subdivided into subgroups I and II in studies by other researchers (Kubota et al, 2020;Wang Y.X. et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…The P1-P4 proteins encoded by GEVA were presumed to be the viral RdRp, GP, CP, and MP due to the presence of similar domains and motifs in homologous proteins from other emaraviruses, however, there was low overall sequence identity of P1-P4 from GEVA with these proteins from other emaraviruses. Furthermore, the phylogenetic tree of RdRp, GP, CP, and MP showed that GEVA was positioned in subgroup I of Emaravirus, as reported by Liu et al (2020), but which was subdivided into subgroups I and II in studies by other researchers (Kubota et al, 2020;Wang Y.X. et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…We did not identify any other RNA of the virus from diseased jujube samples by using different approaches, indicating that RNAs 1-6 might represent the complete genomic components of JYMaV. Prevalent peaks of RNA and sRNA reads on the RNA3 and RNA6 of JYMaV are highly similar to that of pear chlorotic leaf spot-associated virus (PCLSaV), a recently identified emaravirus from pear [31]. Similarly, high levels of vsiRNAs were generated from pigeonpea sterility mosaic emaravirus 1 (PPSMV-1) RNA3 and RNA4 segments [32].…”
Section: Discussionmentioning
confidence: 82%
“…RT-PCR tests also showed that eriophyid mite samples from diseased jujube plants were JYMaV positive, suggesting that eriophyid mites might vector JYMaV and cause the wide distribution of the viral disease at Aksu jujube fields. The high RNA-Seq read numbers within the ORFs of the viral RNA3 and RNA6 might be favorable for developing RNA3-and RNA6-based RT-PCR detection of JYMaV as that for other emaraviruses [31,46].…”
Section: Discussionmentioning
confidence: 99%
“…Polyribosomal RNA was isolated from infected fig leaves, and 5′ rapid amplification of cDNA ends (RACE) was performed identifying 12–18 nt of non-viral RNA sequences at the 5′ end of FMV RNAs [ 93 ]. The polymerase active site consists of six motifs known as the preA, and A through E motifs that lie toward the C-terminal half of the RdRp [ 23 , 94 , 95 ]. The importance of this region for viral RNA synthesis was confirmed by introducing a mutation into the rose rosette virus (RRV) RdRp that debilitated RNA synthesis [ 95 ].…”
Section: Virion Composition Genome Organization and Intracellular Replication Cyclementioning
confidence: 99%